2017
DOI: 10.1039/c7py01606a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high molecular weight elastomeric polyethylene using an electronically and sterically enhanced nickel catalyst

Abstract: Highly active para-t-Bu-containing 1,2-bis(imino)acenaphthene-Ni(ii) catalysts are disclosed which afford hyper-branched PEs with Mw's up to 3.1 × 106 g mol−1; high tensile strength, excellent shape fixity as well as high elongation at break are a feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 74 publications
10
98
0
1
Order By: Relevance
“…The 1 H‐NMR spectra of these Ni (II) ( S = 1) complexes display broad paramagnetically shifted peaks that can be assigned through a comparison with data for related species,[4a] relative integration and closeness to the paramagnetic center (Figures S1–S10). Using Ni1 as an example, the acenaphthene protons can be identified as six distinct signals between δ 4.96 and 24.45, reflecting the presence of the two inequivalent N ‐aryl groups.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The 1 H‐NMR spectra of these Ni (II) ( S = 1) complexes display broad paramagnetically shifted peaks that can be assigned through a comparison with data for related species,[4a] relative integration and closeness to the paramagnetic center (Figures S1–S10). Using Ni1 as an example, the acenaphthene protons can be identified as six distinct signals between δ 4.96 and 24.45, reflecting the presence of the two inequivalent N ‐aryl groups.…”
Section: Resultsmentioning
confidence: 94%
“…The stress–strain curves were obtained using a universal tester (Instron 1122, UK). The stress–strain recovery tests at different temperatures were carried out using a dynamic mechanical analyzer (DMA800, TA) under controlled force mode and performed as described elsewhere [4a,10]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[36,37] The benzhydryl-derived α-diimine nickel catalysts developed by Long et al showed outstanding thermal stability and could form high-molecular-weight polyethylene (M n > 600 000 g mol −1 ) (Figure 1, III). [42,43] According to the FIGURE 1 Selected examples of previously reported α-diimine Ni(II) catalysts literature reports, hyperbranched polyethylene with high molecular weight can be prepared using α-diimine Ni(II) catalysts with bulky substituents on the aniline moieties. [40,41] Recently, Sun et al used a group of unsymmetric αdiimine nickel catalysts to prepare elastomeric polyethylenes that showed good elastomeric recovery and high elongation at break (Figure 1, V).…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] Recently, Sun et al used a group of unsymmetric αdiimine nickel catalysts to prepare elastomeric polyethylenes that showed good elastomeric recovery and high elongation at break (Figure 1, V). [42,43] According to the FIGURE 1 Selected examples of previously reported α-diimine Ni(II) catalysts literature reports, hyperbranched polyethylene with high molecular weight can be prepared using α-diimine Ni(II) catalysts with bulky substituents on the aniline moieties. However, such bulky substituents were found to reduce the branching density of polyethylenes compared with B-Cat.…”
Section: Introductionmentioning
confidence: 99%